PENGAJARAN DASAR AKUNTANSI MELALUI FLIPPED CLASSROOM DALAM KEGIATAN ASISTENSI MENGAJAR DI SMA TARSISIUS 1 JAKARTA - Jennifer, Jennifer; Sriwati, Sriwati (Jurnal Bakti Masyarakat Indonesia, 2025)
The lack of quality in accounting education in Indonesia has become a challenge for the future of the accounting profession. This teaching assistance program was carried out to help improve the quality of accounting education, especially at SMA Tarsisius 1 Jakarta, which faces the issue of limited study time for delivering in-depth accounting material. This has caused students to view accounting as a very complex subject, reducing their interest in it. As a solution, the flipped classroom method was implemented, where students were given learning materials independently outside of class through modules and PPT (PowerPoint presentations). Meanwhile, class time was used for discussions, problem-solving exercises, and direct evaluation of student understanding. The results of this teaching assistance program using this method showed a significant increase in students understanding of basic accounting concepts. Based on quiz evaluations and questionnaire results, this method proved to be effective not only in enhancing understanding but also in increasing active participation and students interest in accounting. The implementation of the teaching assistance program at SMA Tarsisius 1 Jakarta for 6 offline meeting sessions for accounting subjects with the flipped classroom learning method has run according to the objectives and has had a positive impact on various parties. This method is not only a solution to the problems faced by SMA Tarsisius 1 Jakarta in terms of time constraints to deliver materials, but also succeeded in creating a more interactive and enjoyable learning atmosphere. Overall, this teaching method has the potential to become an innovative and effective solution for improving the quality of accounting education in Indonesia ABSTRAK Kurangnya kualitas pendidikan akuntansi di Indonesia saat ini telah menjadi tantangan bagi profesi akuntan di masa depan. Program asistensi mengajar ini dilaksanakan untuk membantu meningkatkan kualitas pendidikan akuntansi, terutama di SMA Tarsisius 1 Jakarta, yang menghadapi masalah keterbatasan waktu belajar untuk penyampaian materi akuntansi secara mendalam. Hal ini membuat siswa menganggap mata pelajaran akuntansi sangat kompleks, sehingga menurunkan minat mereka terhadap akuntansi. Sebagai solusinya, diterapkan metode flipped classroom dimana siswa diberikan materi pembelajaran secara mandiri di luar kelas melalui modul dan PPT (PowerPoint presentations), sementara waktu di kelas digunakan untuk diskusi, latihan soal, serta evaluasi pemahaman secara langsung. Hasil kegiatan asistensi mengajar melalui metode ini menunjukkan adanya peningkatan signifikan dalam pemahaman siswa mengenai konsep dasar akuntansi. Pelaksanaan program asistensi mengajar di SMA Tarsisius 1 Jakarta selama 6 sesi pertemuan luring untuk mata pelajaran akuntansi dengan metode pembelajaran flipped classroom telah berjalan sesuai tujuan dan memberikan dampak positif bagi berbagai pihak. Metode ini tidak hanya menjadi solusi bagi permasalahan yang dihadapi SMA Tarsisius 1 Jakarta dalam keterbatasan waktu untuk menyampaikan materi, tetapi juga berhasil menciptakan suasana belajar yang lebih interaktif dan menyenangkan. Secara keseluruhan, metode pembelajaran ini berpotensi menjadi solusi yang inovatif dan efektif dalam meningkatkan kualitas pendidikan akuntansi di Indonesia.